Puccini's La Bohème - Puccini, Giacomo, 1858-1924 (Opera classics library., 2005)
A comprehensive guide to Puccini's LA BOHEME, featuring insightful and in depth Commentary and Analysis, a complete, newly translated Libretto with Italian/English side-by side, and over 20 music highlight examples.